Joe La Pompe 100 visual ideas, 1000 great ads. - La Pompe, Joe, ....-; Koedinger, Mike, ....- (Luxembourg : Maison Moderne, 2012)
In 100 Visual Ideas, 1000 Great Ads, the French blogger and undercover advertising expert Joe La Pompe exposes the not-so-secret visual recipes behind successful ads. La Pompe extracts the 100 most popular visual ideas and recurring subject s from the world of advertising. He then presents the ten best campaigns from around the world that are based on each of these themes, yet have implemented them in a variety of different ways. By illustrating correlations and inspirations, this book offers advertising agencies and designers informed, entertaining, and often revealing insights into the world of commercial seduction.